1990
DOI: 10.1038/345036a0
|View full text |Cite
|
Sign up to set email alerts
|

The three-dimensional structure of the bacterial virus MS2

Abstract: The structure of the icosahedral bacteriophage MS2 has been determined to 3.3 A resolution by X-ray crystallography. The phase determination involved both molecular replacement at low resolution using a known structure and heavy-atom substitution. The coat protein has no structural similarity to that of any other known RNA virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
370
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(376 citation statements)
references
References 41 publications
5
370
0
1
Order By: Relevance
“…12,20−22 In phage and VLPs, the MS2 CP forms dimers that assemble into an icosahedron with 12 pentameric and 20 hexameric facesa so-called T = 3 geometry. The structure of MS2 particles has been extensively characterized, [23][24][25][26]14 but, as with other multimeric assemblies, no point mutations are known to confer uniform changes in the icosahedral supramolecular structure adopted by the CP. If these could be identified, the mutants would serve as useful tools for exploring the effects of VLP size on engineered MS2 VLP performance for drug delivery and imaging applications.…”
mentioning
confidence: 99%
“…12,20−22 In phage and VLPs, the MS2 CP forms dimers that assemble into an icosahedron with 12 pentameric and 20 hexameric facesa so-called T = 3 geometry. The structure of MS2 particles has been extensively characterized, [23][24][25][26]14 but, as with other multimeric assemblies, no point mutations are known to confer uniform changes in the icosahedral supramolecular structure adopted by the CP. If these could be identified, the mutants would serve as useful tools for exploring the effects of VLP size on engineered MS2 VLP performance for drug delivery and imaging applications.…”
mentioning
confidence: 99%
“…and M.G.R., manuscript in preparation). Difference Fouriers at various resolutions showed that the Babinet opposite solution had been obtained 41,56 . The phases were, therefore, flipped (α → π + α) before plotting the final electron density map.…”
Section: Figmentioning
confidence: 99%
“…The eight-stranded antiparallel virus fold has now been found in many RNA and DNA viral capsids 39 , yet its presence is not entirely universal (for example in the plant RNA tobacco mosaic virus 54,55 , in the RNA phage MS2 56 and in the animal RNA Sindbis virus 57 ). Hence, the eight-stranded antiparallel β-barrel fold is not a prerequisite for assembly of icosahedral structures 58 .…”
Section: Evolutionmentioning
confidence: 99%
“…(9) It is a non-enveloped virus similar in physical characteristics to pathogenic enteroviruses and commonly used as a surrogate for human viruses. An individual MS2 virion is nearly spherical with an average diameter ∼28 nm, making it one of the smallest viruses.…”
Section: Ms2 Virusmentioning
confidence: 99%